The Role of Conflicting Representations and Uncertainty in Internal Error Detection During L2 Learning. (2nd June 2020) - Bultena, Sybrine; Danielmeier, Claudia; Bekkering, Harold; Lemhöfer, Kristin
Abstract: Internal error monitoring as reflected by the error‐related negativity (ERN) component can give insight into the process of learning a second language (L2). Yet, early stages of learning are characterized by high levels of uncertainty, which obscures the process of error detection. We examine how uncertainty about L2 syntactic representations, induced by different levels of language conflict, is reflected in ERN patterns during learning. German learners of Dutch performed a feedback‐guided gender decision task in their L2 and provided subjective certainty ratings for their responses. Initially, high‐conflict items yielded more uncertainty and ERN modulations were reversed (i.e., correct responses elicited larger amplitudes than errors). Two rounds of feedback resulted in an increase of accuracy, reduced uncertainty, and normalization of the ERN effect, signaling effective error monitoring. These outcomes demonstrate how subjective intuitions about response accuracy affect performance monitoring during L2 learning. Abstract :